Resolution of inflammation: Intracellular feedback loops in the endothelium - Winsauer, Gabriele; de Martin, Rainer (Thrombosis and Haemostasis, 2007)
Timely termination of the inflammatory reaction is equally important as its elicitation, since a persistent or exaggerated response may lead to detrimental effects in the affected tissues and organs. Therefore, and in accordance with the complex and highly coordinated activation phase, negative regulatory mechanisms have evolved which function on multiple levels to ensure the appropriate termination of the inflammatory response. This review will focus on the mechanisms that are operative in endothelial cells to shut down the activity of specific signaling pathways and transcription factors that have been activated in response to pro-inflammatory mediators, and provide evidence that the stage for resolution is set already early in the activation phase of the inflammatory response. The elucidation of these feedback mechanisms is of importance for the understanding of acute versus chronic inflammation, and for novel strategies for therapeutic intervention.
Keywords: Endothelial cells; signal transduction; inflammation